Pollen‐induced antigen presentation by mesenchymal stem cells and T cells from allergic rhinitis - Desai, Mauli B; Gavrilova, Tatyana; Liu, Jianjun; Patel, Shyam A; Kartan, Saritha; Greco, Steven J; Capitle, Eugenio; Rameshwar, Pranela (Clinical & translational immunology, 2013)
Mesenchymal stem cells (MSCs) are promising cellular suppressor of inflammation. This function of MSCs is partly due to their licensing by inflammatory mediators. In cases with reduced inflammation, MSCs could become immune‐enhancer cells. MSCs can suppress the inflammatory response of antigen‐challenged lymphocytes from allergic asthma. Although allergic rhinitis (AR) is also an inflammatory response, it is unclear if MSCs can exert similar suppression. This study investigated the immune effects (suppressor vs enhancer) of MSCs on allergen‐stimulated lymphocytes from AR subjects (grass or weed allergy). In contrast to subjects with allergic asthma, MSCs caused a significant (P<0.05) increase in the proliferation of antigen‐challenged lymphocytes from AR subjects. The increase in lymphocyte proliferation was caused by the MSCs presenting the allergens to CD4+ T cells (antigen‐presenting cells (APCs)). This correlated with increased production of inflammatory cytokines from T cells, and increased expressions of major histocompatibility complex (MHC)‐II and CD86 on MSCs. The specificity of APC function was demonstrated in APC assay using MSCs that were knocked down for the master regulator of MHC‐II transcription, CIITA. The difference in the effects of MSCs on allergic asthma and AR could not be explained by the sensitivity to the allergen, based on skin tests. Thus, we deduced that the contrasting immune effects of MSCs for antigen‐challenged lymphocytes on AR and allergic asthma could be disease specific. It is possible that the enhanced inflammation from asthma might be required to license the MSCs to become suppressor cells. This study underscores the need for robust preclinical studies to effectively translate MSCs for any inflammatory disorder. Allergic diseases: Same cell therapy, opposite responses Individuals with allergic inflammation of the nasal airways may respond differently to stem cell therapy than individuals with allergic asthma, a cell‐based study shows. Pranela Rameshwar and her colleagues at the Rutgers University–New Jersey Medical School, USA, tested the effects of adding mesenchymal stem cells (MSCs) to blood samples from subjects with either allergic rhinitis, commonly known as hay fever, or allergic asthma. The researchers first extracted a subset of blood cells containing many important components of the immune system, including peripheral blood mononuclear cells (PBMCs). They then challenged the PBMCs to immune‐triggering antigens such as ragweed, before introducing MSCs. The stem cells had a suppressive effect on the immune system in samples from asthma sufferers, but an immune‐enhancing effect on samples from people with allergic rhinitis — despite the typical inflammatory response being similar in both rhinitis and asthma sufferers.